A qualitative exploration of children’s willingness to take the COVID-19 vaccine in Jordan - Tareq L. Mukattash, Khalid Ahmed Kheirallah, Hadeel Daradkeh, Anan S. Jarab,, Rana K. Abu-Farha, Mohammad B. Nusair, Samar Karout, Rania Itani (Journal of Applied Pharmaceutical Science, 2023)
Vaccine willingness has an important role in COVID-19 adult vaccination programs in many countries. However, there are limited data about vaccine willingness among children, which is largely confined to parents’ opinions. With the emergence of new variants affecting this age group, children’s opinions on COVID vaccination are important. This study aimed to explore children’s willingness and opinions regarding COVID-19 vaccination. Focus group discussions, including children, were carried out in different Jordanian schools. Purposive sampling was implemented to select students of different socioeconomic statuses. A total of 54 school students aged 6–14 years from three schools participated in nine focus groups. Overall, participating children were willing to take the COVID-19 vaccine, and three overarching themes described their view regarding the vaccine: benefits, motivators, and hesitancy and barriers. Participating children reported that the vaccine could be beneficial as it protects them from being infected, and they are motivated to take it as it has been approved for children in other countries. However, some children were hesitant regarding taking the vaccine as it could be harmful, and they believed that COVID-19 is not severe in children. In conclusion, this study shows a clear willingness among participants from primary and secondary schools to take the COVID-19 vaccine. Such outcomes should be tested further on a larger scale to deliver future recommendations to include younger children in the vaccination program.